Fabrication of Spark Plasma Sintered Spark Plasma Sintered Transparent Alumina Using Magnesium Oxide and Lanthanum Oxide as Sintering-Assisted - M. Shahriari; H. Jamali; H. Mansouri; M. R. Loghman Estarki; M. Sardarian (Journal of Advanced Materials in Engineering)
In this research, the fabrication of transparent Alumina was done by spark plasma sintering (SPS). Two types of alpha and gamma Alumina powders with particle size of 200 and 50 nm were used, respectively. The sintering assisted materials used in this research were magnesium nitrate and lanthanum nitrate, each of which was used 100 ppm using a chemical precipitation process. Calcination was performed at 800°C and the resulting powders were subjected to SPS at 1500 °C with a rate of 50 °C/min for 15 minutes under a pressure of 70 MPa. The phase composion was analyzed by X-ray diffraction (XRD) before and after SPS. The morphology of the powders and the microstructure of the sintered samples were studied using scanning electron microscopy (SEM). The bulk density was obtained to be 3.94 gr/cm3 and 3.9 gr/cm3 in the alpha and gamma samples, respectively. The UV-Visible transmission test showed 20% transmission in the alpha alumina sample. The amount of IR transmission in the alpha and gamma samples was obtained to be 65% and 25%, respectively. The alpha alumina sample had a higher transmission percentage and density compared to the gamma sample.